Smart Ruler as an Innovative Medium for Enhancing the Learning Outcomes of TVET Fashion Program Students: Students' and Users' Perceptions of the Smart Ruler as an Innovative Learning Tool - Norulaini Mohd. Ramly; Catherine Nguoi Chui Lam; Muneswary Saminathan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The manual process of clothing pattern drafting presents a major challenge for TVET Fashion Programme students, as conventional methods require excessive time, extreme precision and involve high costs, while carrying a high risk of measurement errors, repetitive and burdensome. Therefore, an innovative tool the Smart Ruler has been developed to overcome these time constraints, reduce operational costs and improve both ergonomics and accuracy in the teaching and learning of clothing pattern drafting. This study was conducted to evaluate the effectiveness of using Smart Ruler in the teaching and learning of clothing pattern drafting among TVET Fashion Programme students. A 4-point Likert scale survey was used to collect data from a total of 20 respondents, comprising lecturers, students, and fashion designers. Descriptive analysis was employed to examine time, cost, physical fatigue, accuracy and work quality. The results indicate that the Smart Ruler saved more than 50% of the time compared to manual practices and reduced costs within a range of RM20 to RM150. The highest mean scores were recorded for explanation of concepts (Mean= 4.0), followed by quality improvement of assignment (Mean = 3.9) and the enhancement of competitiveness within the local fashion industry (Mean = 3.9). Furthermore, physical fatigue levels dropped by 75% compared to manual methods. Ultimately, it can be concluded that the Smart Ruler significantly enhances the effectiveness of teaching and learning for pattern drafting. This innovation not only accelerates the workflow and improves precision but also possesses the potential to be implemented as a standardized teaching aid across the TVET fashion field.